Electrophysiological and Morphological Evidence for a GABAergic Nigrostriatal Pathway - Rodriguez, Manuel; Gonzalez-Hernandez, Tomas (The Journal of neuroscience, 1999)
The electrophysiological and neurochemical characteristics of the nondopaminergic nigrostriatal (NO-DA) cells and their functional response to the degeneration of dopaminergic nigrostriatal (DA) cells were studied. Three different criteria were used to identify NO-DA cells: (1) antidromic response to striatal stimulation with an electrophysiological behavior (firing rate, interspike interval variability, and conduction velocity) different from that of DA cells; (2) retrograde labeling after striatal injection of HRP but showing immunonegativity for DA cell markers (tyrosine hydroxylase, calretinin, calbindin-D28k, and cholecystokinin); and (3) resistance to neurotoxic effect of 6-hydroxydomine (6-OHDA). Our results showed that under normal conditions, 5–8% of nigrostriatal neurons are immunoreactive for GABA, glutamic acid decarboxylase, and parvalbumin, markers of GABAergic neurons, a percentage that reached 81–84% after 6-OHDA injection. Electrophysiologically, NO-DA cells showed a behavior similar to that found in other nigral GABAergic (nigrothalamic) cells. In addition, the 6-OHDA degeneration of DA cells induced a modification of their electrophysiological pattern similar to that found in GABAergic nigrothalamic neurons. Taken together, the present data indicate the existence of a small GABAergic nigrostriatal pathway and suggest their involvement in the pathophysiology of Parkinson’s disease.